The effect of 4-month cycling trainings performed on elite cyclists on some immunological parameters - Fulya Erantgil; Mehibe Akandere (Selcuk University, 2018)
The aim of this study was to investigate some immunological parameters, which showed differences in elite cyclists as a result of four months of chronic cycling trainings. The experimental group in this study consisted of 15 elite level trained cyclists between the ages of 17-19 who participated in international competitions. A regular training program was applied to the cyclists belonging to the experiment group for 6 days a week for 4 months. Prior to four-month chronic training, blood samples of cyclists were taken from the elbow vein. This procedure was repeated four months later. The control group consisted of individuals who did not regularly exercise and their ages were equivalent to the cyclists. No training program was applied to the control group. The data obtained in the study were analyzed statistically with the SPSS computer package software after being transferred to the electronic medium. In order to determine the homogeneity of the obtained data, "Single Sample Kolmogorov-Smirnov" test was performed, and the data was found to show normal distribution. "Independent t" test was used to determine differences between groups, while the analysis of intra-group measurements was performed by "Paired t" test. Significance level was determined as P lt;0.05. Immunoglobulins and leukocyte parameters were measured in the study. In the obtained findings, as a result of the 4-month chronic cycling training in the experimental group, statistically significant difference was found in neutrophil, neutrophil%, lymphocyte, lymphocyte% values before and after training, whereas leukocyte, monocyte, monocyte%, eosinophil, eosinophil%, basophil and basophil% parameters did not display any significant difference (P gt;0.05). Significant differences were observed in IgA, IgG, and IgE parameters, whereas no significant difference was found in IgM parameter (P lt;0.05). When the leukocyte counts of the experimental group and the control group were examined, no significant difference was observed in the lymphocyte, monocyte, monocyte%, eosinophil, eosinophil%, basophil parameters, while a statistically significant difference was detected between leukocyte, neutrophil, neutrophil%, lymphocyte% and basophil% values (P lt;0.05). When the immunological parameters belonging to both groups were examined, it was found that there was a significant difference in the parameters of IgG, IgG, and IgM between the control and experimental group (P lt;0.05). This was not the case for IgE parameter (P gt;0.05). In conclusion, some leukocyte and immunoglobulin parameters were increased in the presence of chronic training. This increase is due to the reaction of the immune system to the training.